Aggregate Quasi Rents and Auditor Independence: Evidence from Audit Firm Mergers in China* - HUNG CHAN, K.; WU, DONGHUI (Contemporary Accounting Research, 2011)
2008 American Accounting Association Annual Meeting in Anaheim, the 2009 Contemporary Accounting Research/Journal of Contemporary Accounting and Economics Special Joint Symposium, and workshops at the Chinese University of Hong Kong and Shanghai University of Finance and Economics for their helpful comments